Thymic B Cells and Central T Cell Tolerance - Yamano, Tomoyoshi; Steinert, Madlen; Klein, Ludger (Frontiers in Immunology, 2015)
Central T cell tolerance is believed to be mainly induced by thymic dendritic cells and medullary thymic epithelial cells. The thymus also harbors substantial numbers of B cells. These may arise though intrathymic B lymphopoiesis or immigration from the bloodstream. Importantly, and in contrast to resting ‘mainstream’ B cells in the periphery, thymic B cells display elevated levels of MHC class II and constitutively express CD80. Arguably their most unexpected feature is the expression of Aire. These unique features of thymic B cells result from a licensing process that involves cross-talk with CD4 single-positive T cells and CD40 signaling. Together, these recent findings suggest that B cells play a more prominent role as thymic APCs than previously appreciated.